Evaluating the role of customization and information enrichment strategies on trust and purchase: The moderating role of intelligence in enhancing consumer experience (case study: Online store customers) - Hossein Balouchi; Eesa Niazi; Mohammad Ali Siah Sarani Kojouri (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The current research examines the impact of customization and information richness strategies on customer trust and purchase intention on e-commerce websites, as well as the moderating role of business intelligence in these processes.Methodology: His research is applied in its purpose and correlational in its method. The statistical population consisted of buyers from the Digikala and TechnoLife websites. The minimum sample size based on structural equation modeling sampling methods was 375 individuals, and a sample of 385 buyers from these websites was collected. Data collection was done using a questionnaire. The reliability of the questionnaire was confirmed using Cronbach's alpha, composite reliability, and convergent validity (extracted variance), and discriminant validity (Fornell-Larcker criterion and HTMT ratio). Statistical analyses were conducted using Smart PLS 4 software and the PLS-SEM approach.Findings: The results indicated that trust positively affects purchase intention, and service customization influences purchase intention through trust. Information richness also affects purchase intention both directly and through trust. Business intelligence had a negative impact on the relationship between service customization and trust but did not have a significant effect on the relationship between information richness and trust.Originality/Value: This refers to the work you are doing from your perspective, even though you may support your arguments with research conducted by others.